The Influence of Teamwork and Work Discipline on Employee Performance: A Quantitative Study at Ananda Maternity and Children's Hospital, Makassar - Dian Anggraeni Rachman; Sri Reski Astuti; Nurul Fajriah Istiqamah (Pancasakti Journal Of Public Health Science And Research, 2025)
Human resources are a critical component that every organization must prioritize, as they play a vital role in determining the success of the organization in achieving its goals. This study aims to examine and analyze the influence of teamwork and work discipline on employee performance at RSIA Ananda in Makassar City. A quantitative research approach was employed, with data collected through the use of questionnaires. The population of the study consisted of 317 employees at RSIA Ananda Makassar. Using purposive sampling, a total of 177 respondents were selected as the sample. Data testing included both validity and reliability tests to ensure the quality of the instrument. The data were analyzed using multiple linear regression, with hypothesis testing conducted through the F-test. The results of the F-test showed that the calculated F value was 228.477, which exceeds the critical F value of 3.05, and the significance level was 0.000, which is below the threshold of 0.05. These findings indicate that teamwork and work discipline have a statistically significant simultaneous effect on employee performance. Moreover, the results demonstrate that both teamwork and work discipline contribute to employee performance at RSIA Ananda Makassar, with work discipline emerging as the dominant influencing factor.